PERAN MASYARAKAT SEBAGAI MITRA POLRI DALAM MENCEGAH RADIKALISME DI MASYARAKAT - Putranto, Faizal; Yudha Utama, Jenny; Sidharta Arisandi, Rachman (Universitas Islam Majapahit, Indonesia, 2023)
Indonesia is a country rich in culture, ethnicity, nation and religion. One of the shakers of unity and integrity in Indonesiais the existence of an ideology of radicalism. One strategy to overcome radicalism is to collaborate with community organizations, whichone of them is Sholaya Park. This research uses a descriptive qualitative method and aims to determine the role of Sholaya Parkin preventing radicalism in society. This research analysis uses the Hegemony theory of Antonio Gramsci and Louis Althusser regarding the StateApparatus. The conclusion of this research is that Taman Sholaya as an ideological State Apparatus collaborates with the police as a Responding StateApparatus in hegemonizing society through Cultural, Intellectual and Crisis approaches. However, Sholaya Park's role is in preventingradicalism is only limited to the congregation and the surrounding community